ANALISIS PENGEMBANGAN PEGAWAI DAlAM RANGKA MENINGKATKAN EFEKTIVITAS KERJA PADA INSTANSI PEMERINTAH - Rifai Yusuf (Universitas Swadaya Gunung Jati, 2013)
Every organization, including government organizations and local government wants tercapivision and mission in a satisfactory manner, in order to achieve that purpose, support humanresource professional and proportionate. to improve the work of the employees, throughemployee development programs that need to be done in a planned and sustainable,Employee development menfaatnya be felt increasingly important because of the demands ofthe job or position, as a result of technological advancement, every employee is required towork effectively, efficiently, the quality and quantity of workthat employee development is done for the purpose of nonkarier and career to new or existingemployees through training and education, promotion and transfer, as a competent and skilledemployees will be able to work more efficiently, effectively.So that the effectiveness of the work is the state that shows ketercapaiannya a governmentagency goals previously set by mobilizing all the resources contained on the people throughits activities.To achieve high work effectiveness and facilitate reaching goals can not be separated fromthe program staff development through education, training, promotion and transfer.